Italy : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper establishes a causal link between public sector efficiency at the provincial level and firm productivity using data for about 450,000 Italian firms. It emphasizes that significant productivity gains could be realized if public sector efficiency improves from currently low levels. If efficiency rises to the frontier in all provinces, output per employee would increase 9 percent for the average firm. Implementing the public administration reform agenda and recommendations of the 2014 spending review and competition authority could help deliver some of these productivity gains.